Intercalation of fullerite C60 with N2 molecules. An investigation by x-ray powder diffraction
The lattice parameter a of fullerite C60 intercalated with N2 molecules is investigated in the temperature interval 6-295 K by x-ray diffraction. It is found that the interstitial molecular N2 has a considerable effect on both the temperatures, Tc of the orientational phase transition and Tg of the orientational glass formation. Hysteresis of a(T) has been detected in the Tc and Tg regions, besides, the abrupt change in the volume over the region defining Tc. Complete intercalation of C60